Design of a precision battery charge meter - Najihah Abdul Razak (2019)
This project involves implementing a coulomb counter to obtain accurate data measurements of a battery. This includes the Charge, Current, Voltage, State-of-Charge with addition of the timestamps for each measurement taken. The purpose of this is to further understand the behaviour of batteries in hopes of extending the lifecycle of rechargeable batteries. The discharging circuit design is set up to accommodate to the safety precautions needed to be taken when discharging the battery for its measurements.